2021
DOI: 10.54055/ejtr.v27i.2139
|View full text |Cite
|
Sign up to set email alerts
|

The adoption of self-service kiosks in quick-service restaurants

Abstract: This study investigates factors influencing the customers’ decision to use self-service kiosks in quick service restaurants. A model incorporating Technology Acceptance Model and Satisfaction Model was developed to examine the relationships among trust, self-efficacy, perceived ease of use, perceived usefulness, perceived enjoyment, perceived value, satisfaction and behavioural intention toward using these kiosks. The moderating impact of age, gender and past self-service kiosks experience was also examined. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 72 publications
(108 reference statements)
0
12
0
2
Order By: Relevance
“…perceived usefulness, ease-of-use, credibility, and subjective norm) and intention to use hotel tablet apps. A recent kiosk study in a restaurant setting (Rastegar et al, 2021) also demonstrated a similar finding that age did not moderate the relationships between three predictors (i.e. perceived ease of use, usefulness, and enjoyment) and two dependent variables (i.e.…”
Section: Effect Of Agementioning
confidence: 68%
“…perceived usefulness, ease-of-use, credibility, and subjective norm) and intention to use hotel tablet apps. A recent kiosk study in a restaurant setting (Rastegar et al, 2021) also demonstrated a similar finding that age did not moderate the relationships between three predictors (i.e. perceived ease of use, usefulness, and enjoyment) and two dependent variables (i.e.…”
Section: Effect Of Agementioning
confidence: 68%
“…For instance, Hao and Chon (2021) stated that a Hong Kong-based survey company collected the data for the study; however, did not specify the name of the company. Other studies like Mason et al (2021) , Palumbo (2022) , and Rastegar et al (2021) specified the museums and/or platforms (MTurk, Qualtrics, and others) as data collection sites.…”
Section: Future Research Suggestionsmentioning
confidence: 99%
“…We define cashier-less stores as physical stores with no human interaction during the check-out process, aligning with the "just walk out" format (Cui et al, 2021). The launch of Amazon's first cashier-less store on January 22, 2018 (Zhang et al, 2019), capitalizes on the "Just Walk Out" technology to offer an AI-enabled retailing experience that is convenient (Rastegar, 2018) and empowers consumers to alleviate their frustrations of waiting in line, interacting with others and carrying cash (Cui et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The launch of Amazon's first cashier-less store on January 22, 2018 (Zhang et al. , 2019), capitalizes on the “Just Walk Out” technology to offer an AI-enabled retailing experience that is convenient (Rastegar, 2018) and empowers consumers to alleviate their frustrations of waiting in line, interacting with others and carrying cash (Cui et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%